Extraction and sequential elution of a heavy oil from direct coal liquefaction. (15th January 2020) - Gao, Hua-Shuai; Zong, Zhi-Min; Yang, Zheng; Huang, Li-Li; Zhang, Min; Teng, Dao-Guang; Wei, Xian-Yong
Highlights: MWAE and subsequent SE are effective for enriching condensed aromatics from HODCL . HODCL mainly consists of tricyclic and tetracyclic CAs along with small amounts of NAs. Pure pyrene and 1-methylpyrene were separated by MWAE and subsequent SE from HODCL . Abstract: Microwave-assisted extraction (MWAE) with CH3 OH and sequential elution (SE) of a heavy oil (HO) from direct coal liquefaction of Heishan bituminous coal combined with subsequent analyses were conducted to understand the molecular composition of the HO and to explore the possibility of separating pure condensed arenes (CAs) from the HO. The yield of extractable portion (EP) from the HO by the MWAE is 94.2% and the main gas chromatograph/mass spectrometer (GC/MS)-detectable compounds in EP are CAs, especially tricyclic and tetracyclic arenes, along with small amount of normal alkanes. By the SE, much more other types of compounds, e.g., oxygen-, nitrogen-, or sulfur-containning organic compounds, were detected with GC/MS, and pyrene and 1-methylpyrene were separated in the purities of 95.2% and 93.4%, respectively.